Consistency of stand density estimates and their variability in forest inventories in Slovenia - Hladnik, David (Acta silvae et ligni, 2014)
The national estimates of forest resources in Slovenia are based on data aggregation from forest inventories conducted in forest management units of Slovenia Forest Service (SFS) and on the parallel forest inventory established within the Forest and Forest Ecosystem Condition Survey (FECS) as a continuation of international forest monitoring programme. Since the difference in sampling design and temporal dynamics of data collection is of key importance for inventories at the level of forest management units compared to large-area forest inventories, the consistency of stand densities was checked in both concepts. Comparing growing stock estimates in FECS on the systematic 4-km grid of sampling plots from SFS forest management planning, no overall significant differences in temporally comparable periods have been detected. We propose a basis enabling consistent estimates of structural forest characteristics at the national level for the process of forest inventory harmonization in Slovenia.
Keywords: gozdne inventure; vzorčne mreže; sestojne gostote; gozdni rastiščni tipi; Slovenia; Slovenija